Using Gender to Critique the Law - Fernández Revoredo, Marisol (2006)
The eradication of gender-based stereotypes and discriminatory practices is a fundamental social commitment. One of the measures to achieve this objective is found in education. Therefore, this article emphasizes the relevance of incorporating the gender perspective in the study and teaching of law, using this approach as a critical tool to question traditional legal structures. In this context, it is essential to examine the manner in which the gender perspective affects the laws and legal system, particularly in those areas of law that are of critical importance, such as constitutional, labor, family, and criminal law. It is therefore proposed that legal education should include a gender perspective, which will enable future professionals to comprehend and address gender inequalities in Peruvian legislation, thereby facilitating significant transformations in the legal field.